Genetic Programming 19th European Conference, EuroGP 2016, Porto, Portugal, March 30 - April 1, 2016, Proceedings - Heywood, Malcolm I.; McDermott, James; Castelli, Mauro; Costa, Ernesto; Sim, Kevin; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book constitutes the refereed proceedings of the 19th European Conference on Genetic Programming, EuroGP 2016, held in Porto, Portugal, in March/April 2016 co-located with the Evo*2016 events: EvoCOP, EvoMUSART, and EvoApplications. The 11 revised full papers presented together with 8 poster papers were carefully reviewed and selected from 36 submissions. The wide range of topics in this volume reflects the current state of research in the field. Thus, we see topics as diverse as semantic methods, recursive programs, grammatical methods, coevolution, Cartesian GP, feature selection, metaheuristics, evolvability, and fitness predictors; and applications including image processing, one-class classification, SQL injection attacks, numerical modelling, streaming data classification, creation and optimisation of circuits, multi-class classification, scheduling in manufacturing and wireless networks.
Keywords: Algorithms; Computer science; Artificial intelligence; Application software; Computer science -- Mathematics; Discrete mathematics; Algorithms; Theory of Computation; Artificial Intelligence; Computer and Information Systems Applications; Discrete Mathematics in Computer Science